The Effectiveness of the Combination of Cucumber (Cucumis sativus) and Mint Leaves (Mentha piperita) Infused Water in Relieving Nausea and Vomiting in Pregnant Women at the Prima Melati Clinic, Medan in 2026 - Fitriyana Br Kaban; Verawaty Fitrinelda Silaban (Jurnal Maternitas Kebidanan, 2026)
Purpose: This study aimed to determine the effectiveness of the combination of cucumber infused water (Cucumis sativus) and peppermint leaves (Mentha piperita) in reducing nausea and vomiting in pregnant women at Klinik Prima Melati Medan in 2026. Design/Methods/Approach: This study used a quasi-experimental design with a pre-test and post-test with a control group approach. The sample consisted of 30 first-trimester pregnant women with nausea-vomiting complaints, divided into 15 intervention groups and 15 control groups by purposive sampling. The intervention group received cucumber and mint infused water 250 mL three times daily for 7 days. Nausea-vomiting was measured using the PUQE (Pregnancy Unique Quantification of Emesis) scale. Findings/Results: There was a significant reduction in PUQE scores in the intervention group (pre-test mean 11.47 vs post-test 5.13, p = 0.000), while the control group showed no significant change (p = 0.312). The independent t-test confirmed a significant difference between groups (p = 0.000). Conclusions: The combination of cucumber and mint infused water is effective in reducing nausea and vomiting in first-trimester pregnant women. This non-pharmacological intervention is safe, easy to implement, and affordable, making it a viable complementary therapy in antenatal care.